Perspectives on performance anxiety in young athletes and dancers - David R. McDuff; Michelle Garvin; Reese Marsalis (Sports Psychiatry)
Abstract: Introduction: Competitive Performance Anxiety (CPA) is commonly seen in sports psychiatry and performance psychology practices that provide services to young athletes and dancers. Rates in this population have risen over the past decade due to rapid progression to the highest competitive levels, early specialization, and year-round training. CPA presents during competition with overthinking, anxious arousal, somatic distress, and behavioral responses that interfere with the execution of critical motor skills and routines and that eventually erode confidence and reduce performance consistency. Methods: This paper reviews the literature on CPA in youth athletes and dancers and presents a clinical model that breaks down the common presentations of CPA into cognitive, emotional, somatic, and behavioral domains. Anonymized cases from the practices of a sports psychiatrist and performance psychologist are presented to illustrate the variability in manifestations, common co-morbid conditions, treatment approaches, and outcomes. The integrated use of brief psychotherapies and adjunctive use of psychiatric medications is discussed. Results: Six CPA cases from individual and team sports and dance are presented and discussed. The use of mental skills training and cognitive behavioral and acceptance and commitment therapies are detailed. The short-term use of beta blockers and selective serotonin reuptake inhibitors and other antianxiety medications is described. The outcomes of each case resulted in reduced anxiety and improved performance consistency. Conclusions: CPA is a common problem in youth athletes and dancers but responds well to brief psychotherapy and medication management. Slow to respond cases often have other co-morbid psychiatric disorders and these must be identified and treated as well.